2020
DOI: 10.3390/jcm9082516
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Prolonged Monitoring of Trauma Patients Admitted via Trauma Resuscitation Unit without Primary Proof of Severe Injuries

Abstract: Introductio: Although management of severely injured patients in the Trauma Resuscitation Unit (TRU) follows evidence-based guidelines, algorithms for treatment of the slightly injured are limited. Methods: All trauma patients in a period of eight months in a Level I trauma center were followed. Retrospective analysis was performed only in patients ≥18 years with primary TRU admission, Abbreviated Injury Scale (AIS) ≤ 1, Maximum Abbreviated Injury Scale (MAIS) ≤ 1 and Injury Severity Score (ISS) ≤3 after treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Therefore, the targeted and reasonable use of these resources is of upmost importance. Heinrich et al showed in a retrospective analysis that slightly injured patients (Abbreviated Injury Scale (AIS) ≤ 1, Maximum Abbreviated Injury Scale (MAIS) ≤ 1 and Injury Severity Score (ISS) ≤ 3) might not need to complete a ≥24 h monitoring [18]. In the light of the economic use of resources, the importance of predicting risk factors associated with specific injury pattern as well as an analysis of the need for extended diagnostic procedures are presented by two further manuscripts of this Special Issue [19,20].…”
mentioning
confidence: 99%
“…Therefore, the targeted and reasonable use of these resources is of upmost importance. Heinrich et al showed in a retrospective analysis that slightly injured patients (Abbreviated Injury Scale (AIS) ≤ 1, Maximum Abbreviated Injury Scale (MAIS) ≤ 1 and Injury Severity Score (ISS) ≤ 3) might not need to complete a ≥24 h monitoring [18]. In the light of the economic use of resources, the importance of predicting risk factors associated with specific injury pattern as well as an analysis of the need for extended diagnostic procedures are presented by two further manuscripts of this Special Issue [19,20].…”
mentioning
confidence: 99%